Self-Assembled Molecules - New Kind of Protein Ligands Supramolecular Ligands (Springer International Publishing, 2018)
This book is an open access under a CC BY license. The subject of this book relates to protein ligands with particular structural and complexation properties. They are composed of self-assembled molecules, capable of penetrating as a unit into proteins outside the binding site. The ribbon-like supramolecular system only permits the penetration of self-assembled molecules into the protein-body and formation of stable complexes. Supramolecular Congo red and similar compounds fit these requirements. Destabilized protein fragments enable the penetration of such ligands, with susceptibility to supramolecular ligand binding often associated with protein function. As a result, complexation modifies their functional effects. The activity of enzymes is inhibited by arresting them in the complexed state, but "naturally irreversible" complexation as in the case of immune complexation, is enhanced instead. This property offers many attractive possibilities of using supramolecular ligands as described in this book.